Peranan Organisasi Notaris dalam Pengawasan Etika Profesi di Kabupaten Sleman - Faisal Ibnu Hasnan (Majelis: Jurnal Hukum Indonesia, 2025)
The role of notary organizations is critical in the continuous development and supervision of the notary's position, especially concerning personal behavior, both in carrying out office duties and in daily life. The notary profession holds a significant position in the legal framework of society as it produces authentic deeds that carry the highest probative value. As such, integrity and professional ethics are foundational principles in the execution of notarial duties. This research aims to analyze the role of notary organizations, specifically the Indonesian Notary Association (INI) in Sleman Regency, in reinforcing professional ethics and maintaining the quality of legal services for the public. The research employs a normative-sociological approach, utilizing studies of legal regulations, notary electronic codes, and interviews with INI Sleman administrators. The findings indicate that notary organizations contribute through (1) socializing ethical codes and professional standards, (2) conducting internal supervision through honorary councils, (3) providing ethical sanctions for violations, and (4) offering development programs and capacity-building initiatives for members. However, the study also identifies several challenges, including limited supervisory resources, resistance from some members, and a lack of public understanding regarding the importance of professional ethics. These obstacles hinder the full potential of notary organizations in ensuring professional conduct and upholding the quality of notarial services. The research underscores the need for stronger collaboration and awareness to address these issues.